KONSELING BEHAVIORAL DENGAN TEKNIK MODELING UNTUK MENINGKATKAN SELF ACHIEVEMENT - Cahyuni, Nurul Ardhia; Tirka, I Wayan; Suranata, Kadek (Universitas Pendidikan Ganesha, 2019)
This study aims to determine the effectiveness of behavioral counseling with modeling techniques to improve self achievement in class VII I Junior High School 3 Singaraja. This type of research is quasi-experimental with pre-test and post-test control group design. These samples included 68 students (male 34 and female 34, average age 12.5 years). Through random sampling, 34 students were placed in the experimental group who received treatment with behavioral counseling and modeling techniques, 34 students as a control group not received treatment. The results of the data analysis are the value of thit 2.978 > ttab 2.021 so that Ho is rejected and Ha is accepted. So there are significant differences. It can be concluded that behavioral counseling with modeling technique is effective for increasing self achievemet in class VII I Junior High School 3 Singaraja.Keywords: Behavioral Counseling, modeling, self achievement